Edukasi Peran Sains dan Matematika di Era Modern di Pesantren Bi’satul Islamiyah - Aslamiah, Aslamiah; Lubis, Nisa Cahya Pertiwi; Suadi, Suadi; Sahyoni, Sahyoni; Siregar, Ayu Meita Puteri; Hayati, Nisma (Jurnal Pengembangan dan Pengabdian Masyarakat Multikultural, 2024)
Due to the massive acceleration of information technology in recent time, the role of science and mathematics, are fundamental. Both are generally not considered crucial for some people, particularly by youth who study at Islamic teachings based traditional school, in this term it is Pesantren Bi’satul Islamiyah. Time allocation and frequency of the subject delivery of mathematics and general sciences are rated far from an ideal compared to the religious based subjects. This community service is a program on conducting the enlightenment on the important role of science and mathematics to be learned by students and triggering the perception that science and mathematics is one of successful keys in the coming time. In executing the program in the field, the lecturers actively delivered by turn the material about the important role of science and Mathematics. This community service shows that students at Pesantren Bi’satul Islamiyah enthusiastically listened and participated the program about the important role of science and mathematics to be learned at their school and building their awareness on the important role of science and mathematics which contributed to their future success. Keyword: Educating, Science, Mathematics, Pesantren Bi’satul Islamiyah